Pentingnya Penerapan Etika Profesi Teknik Sipil dalam Pengambilan Keputusan Resiko Keselamatan dan Kesehatan Kerja & Lingkungan (K3L) - Aditya Imam Wibisono; Albani Musyafa (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the importance of applying professional ethics in civil engineering for decision-making related to safety, health, and environmental risks (K3L). This is crucial because, like other professions, civil engineering is a complex and intricate field that requires not only engineers with good technical skills but also sound decision-making abilities. The decision-making process significantly impacts the execution of infrastructure projects. Professional ethics serve as a guideline for engineers in making decisions that consider K3L. The issue is that decision-making is not solely based on technical skills but also on other soft skills such as emotional control. This study found that emotional intelligence (EQ) can influence the decision-making process of engineers. The higher an engineer's emotional intelligence, the better their decision-making regarding K3L risks. This is also related to engineers adhering to the professional code of ethics. Furthermore, good decision-making processes are expected to promote sustainable infrastructure development.